“JARING KEMISKINAN MASYARAKAT PENJARING”: (STUDI ANALISIS PELANGGENGAN KEMISKINAN PESISIR DI INDONESIA MENURUT TEORI RUANG LEFEBVRE DAN TEORI FUNGSI KEMISKINAN GANS) - MZ, Wahyudhia Zalpa (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2023)
Indonesia is an archipelago country with a total sea area of 3.25 million km2. This makes Indonesia rich in marine resources. However, based on data, fishermen are one of the poorest occupations in Indonesia. This is a tragedy where Indonesian fishermen should be able to live prosperously considering the wealth of natural resources they have, but instead, they live in a web of poverty. Previous studies have explained that poverty in coastal areas is caused by various factors, one of which is structural factors. This paper is a literature study that examines the poverty of coastal communities by emphasizing the structural and functionalist factors of coastal poverty. This paper aims to explain coastal poverty as something that is 'deliberately' produced and perpetuated by the government. Lefebvre's theory of spatial production and Gans' function of poverty are two theories that serve as guidelines in analyzing the phenomenon of poverty. Case examples that occur in Indonesia's coastal areas are presented to strengthen the argument about the perpetuation of poverty. This paper concludes that coastal poverty is a multidimensional poverty. Coastal poverty provides several benefits for other groups. Many development programs carried out by the government ignore the position of local communities. The lack of infrastructure also plays a big role in this. The government, which is supposed to empower coastal communities, seems to 'deliberately' isolate them and utilize them for capitalist interests.